2009
DOI: 10.4236/jbise.2009.24036
|View full text |Cite
|
Sign up to set email alerts
|

Frequency sensitivity of nanosecond pulse EMF on regrowth and hsp70 levels in transected planaria

Abstract: Purpose: To study the effect of time varying/ pulsing electromagnetic fields (PEMF) on bio-logical systems by measuring regrowth and the induction of elevated levels of the stress protein hsp70 in the regenerative model Planaria Duge-sia dorotocethala. Objective: The outcomes of studies using electromagnetic fields (EMF) are dependent on pulse design, field strength (mG), frequency (Hz), duration and magnetic field/rise time (dB/ dt). Standardization of effective pulse design is necessary to avoid continuing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…Different amplitudes (as low as 40 nT) and frequencies (1, 3, 7, 32, and 60 Hz) exhibited stimulatory capacity while others did not. Madkan et al [] also reported differential rates for growth, depending upon the employed frequencies (8, 16, and 72 Hz) in planarian exposed after transection to nanosecond pulsing electromagnetic fields (EMFs) for 1 h daily. There was a general increase in heat shock protein (hsp) 70 in the tail portions of the segments when they were exposed to any of the three frequencies and durations between 20 and 80 min [Madkan et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different amplitudes (as low as 40 nT) and frequencies (1, 3, 7, 32, and 60 Hz) exhibited stimulatory capacity while others did not. Madkan et al [] also reported differential rates for growth, depending upon the employed frequencies (8, 16, and 72 Hz) in planarian exposed after transection to nanosecond pulsing electromagnetic fields (EMFs) for 1 h daily. There was a general increase in heat shock protein (hsp) 70 in the tail portions of the segments when they were exposed to any of the three frequencies and durations between 20 and 80 min [Madkan et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Madkan et al [] also reported differential rates for growth, depending upon the employed frequencies (8, 16, and 72 Hz) in planarian exposed after transection to nanosecond pulsing electromagnetic fields (EMFs) for 1 h daily. There was a general increase in heat shock protein (hsp) 70 in the tail portions of the segments when they were exposed to any of the three frequencies and durations between 20 and 80 min [Madkan et al, ]. Goodman et al [] confirmed that exposure for 1 h twice per day to 60 Hz, 8 µT magnetic fields during the initial 3 days post‐surgery caused increased regeneration.…”
Section: Introductionmentioning
confidence: 99%